Investigations on Tribological Performance of Jatropha Oil Enriched with Polymers under Different Working Conditions - Anthony Chukwunonso Opia; Mohd Fadzli Bin Abdollah; Hilmi Amiruddin (Tribology Online, 2024)
This study examined the effects of polytetrafluoroethylene (PTFE) and Eichhornia crassipes carboxymethyl cellulose (EC-CMC) polymers in base jatropha lubricant and employed commercial shell lubricant as the reference. Wear reduction and coefficient of friction (COF) were measured using 1 mass% polymer concentrations. Characterization analysis showed that the formulation processes required functional groups like carbonyl, alkene, aliphatic CH2 and CH3 group that the Fourier Transmission Infrared (FT-IR) studies indicated were necessary for lubrication. According to the frictional analysis, the polymers’ tribological performance was influenced by changes in both load and operational speed. At 40 kg and 1200 rpm, PTFE and EC-CMC reduced COF by 53.7% and 49.8%, respectively, compared to base jatropha. However, commercial shell oil produced exceptional performance.